Tapping capital markets and institutional investors for infrastructure development - Mathieu Verougstraete; Alper Aras (Asia-Pacific Sustainable Development Journal, 2019)
The present paper is focused on using capital markets in the Asia-Pacific region to channel more resources for infrastructure development, while mobilizing assets managed by institutional investors, such as pension funds and insurance companies. To this end, the paper is structured as follows. First, an analysis of the level of capital market development in the region is conducted, which indicates that markets remain at a nascent stage in many economies. Banks continue to dominate private financing in the region. Second, a review is carried out on the size of institutional investors from which it is suggested that prudential regulation might need to be adjusted to enable greater infrastructure investment. Third, different modalities for investors seeking infrastructure exposure are highlighted and initiatives launched by different countries to support the development of infrastructure-related instruments are presented. Fourth, a review is made on the actions to support capital market development, which is critical for greater involvement of institutional investors. Fifth, ways to address constraints hindering infrastructure investments are presented. Finally, the paper concludes with proposals of strategies that are adapted to each country’s circumstances and designed to further tap this source of financing for infrastructure development.